Helminthostachys zeylanica alleviates hepatic steatosis and insulin resistance in diet-induced obese mice - Ting-Chen Chang; Hao Chiang; Yu-Heng Lai; Yu-Ling Huang; Hsiu-Chen Huang; Yu-Chih Liang; Hui-Kang Liu; Cheng Huang (BMC, 2019)
Abstract Background Obesity and its associated health conditions, type 2 diabetes mellitus (T2DM) and nonalcoholic fatty liver disease (NAFLD), are worldwide health problems. It has been shown that insulin resistance is associated with increased hepatic lipid and causes hepatic steatosis through a myriad of mechanisms, including inflammatory signaling. Methods Helminthostachys zeylanica (HZ) is used widely as a common herbal medicine to relieve fever symptoms and inflammatory diseases in Asia. In the present study, we evaluated whether HZ has therapeutic effects on obesity, NAFLD and insulin resistance. The protective effects of HZ extract were examined using free fatty acid-induced steatosis in human HuS-E/2 cells and a high-fat diet-induced NAFLD in mice. Results The major components of the HZ extract are ugonins J and K, confirmed by HPLC. Incubation of human hepatocytes, HuS-E/2 cells, with palmitate markedly increased lipid accumulation and treatment with the HZ extract significantly decreased lipid deposition and facilitated AMPK and ACC activation. After 12 weeks of a high-fat diet with HZ extract treatment, the HFD mice were protected from hyperlipidemia and hyperglycemia. HZ extract prevented body weight gain, adipose tissue expansion and adipocyte hypertrophy in the HFD mice. In addition, fat accumulation was reduced in mice livers. Moreover, the insulin sensitivity-associated index, which evaluates insulin function, was also significantly restored. Conclusions These results suggest that HZ has a promising pharmacological effect on high-fat diet-induced obesity, hepatic steatosis and insulin resistance, which may have the potential for clinical application.